Validated prediction of weld residual stresses in austenitic steel pipe girth welds before and after thermal ageing, part 1: Mock-up manufacture, residual stress measurements, and materials characterisation. (May 2019) - Smith, M.C.; Muránsky, O.; Xiong, Q.; Bouchard, P.J.; Mathew, J.; Austin, C.
Abstract: A series of engineering-scale multi-pass pipe girth weld mock-ups were manufactured using conventional manual metal arc techniques from Esshete 1250 austenitic steel. They were characterised in detail, in order to provide validation benchmarks for finite element prediction of weld residual stresses. The fabrication sequence comprised initial solution heat treatment and quenching, manufacture of five closely spaced girth welds in a single assembly, and then separation into five individual weldments. Detailed welding records were kept, to allow subsequent calibration of weld heat source models. Residual stresses were measured using diverse methods (incremental deep hole drilling and the contour method), in both the as-welded condition and after thermal ageing at 650 °C. The measurements showed good agreement, providing reliable validation targets for predicted residual stresses in both states. Detailed mechanical property characterisation was performed on both parent material and weld metal, comprising monotonic and isothermal cyclic testing over a range of temperatures from ambient up to 1000 °C. The test data were used to derive a range of Lemaitre-Chaboche mixed isotropic-kinematic model parameter sets for use in finite element simulation. These welds and their supporting characterisation comprise a reliable benchmark for weld residual stress simulation in an engineering-scale weldment. Highlights: Pipe butt weld mock-ups are manufactured to act as validation benchmarks for residual stress simulation. Detailed materials testing is undertaken and mixed isotropic-kinematic hardening models are fitted to the data. Residual stress measurements are performed using diverse techniques in the as-welded state and after high temperature ageing.